Regulatory overkill? Short-sales ban in Korea. Issue 5 (10th October 2016) - Kim, Jaemin; Kim, Joon-Seok; Yoo, Sean Sehyun
Abstract : Purpose: The authors investigate the 2008-2009 short-sales ban in Korea, one of the most comprehensive and restrictive short-selling bans worldwide. The purpose of this paper is to examine: whether the ban stopped a destabilizing effect, if there was any, of short-selling activities; whether the ban improved or deteriorated the informational efficiency or the price discovery process of the stock market; and whether the ban had any impact on market liquidity. Design/methodology/approach: Multiple regression; vector autoregression analysis; and generalized autoregressive conditional heteroskedasticity analysis. Findings: The authors find no evidence that short-sales have a market-destabilizing effect and thus, restricting short-selling has a market-stabilizing effect. On the contrary, the short-selling ban is associated with an increase in return volatility and a deterioration of the price discovery process, particularly for the stocks without derivatives traded on them. The authors also find evidence of a liquidity decrease for short-sale intensive stocks. However, the evidence is inconclusive as to whether the market efficiency and liquidity changes are solely the result of the short-sales ban or the compound effects of both the ban and the concurrent progress of the financial crisis. Originality/value: The literature does not provide a conclusive view on the effects of short-sales or restrictions thereof on the stock market. Also, the existing research on recent worldwide shorting bans often lack empirical scope (e.g. 32 stocks for UK; three weeks for USA). In contrast, the short-sales ban in the Korean stock market, one of the most comprehensive and restrictive short-selling bans worldwide, lasted for eight months for all the listed stocks and is still in effect for financial stocks. The authors find no evidence that short-sales have a market-destabilizing effect and thus, restricting short-selling has a market-stabilizing effect.